Metabolomic Description of Ivacaftor Elevating Polymyxin B Mediated Antibacterial Activity in Cystic Fibrosis Pseudomonas aeruginosa - Allobawi, Rafah (ACS Pharmacol Transl Sci, 2020)
[Image: see text] We have demonstrated that ivacaftor displays synergistic antibacterial activity in combination with polymyxin B against polymyxin-resistant Pseudomonas aeruginosa that commonly colonizes the lungs of people with cystic fibrosis (CF). However, the underlying mechanism(s) remain unclear. In the present study, we employed untargeted metabolomics to investigate the synergistic killing mechanism of polymyxin B in combination with ivacaftor against a polymyxin-susceptible P. aeruginosa FADDI-PA111 (polymyxin B MIC = 2 mg/L) and a polymyxin-resistant CF P. aeruginosa FADDI-PA006 (polymyxin B MIC = 8 mg/L). Metabolites were extracted at 3 h after treatments with polymyxin B alone (2 μg/mL for FADDI-PA111 and 4 μg/mL FADDI-PA006 P. aeruginosa), ivacaftor alone (8 μg/mL), and in combination. Polymyxin B monotherapy induced significant perturbations in the glycerophospholipid and fatty acid metabolism pathways against FADDI-PA111 and to a lesser extent in FADDI-PA006. In both strains, treatment with ivacaftor alone induced more pronounced perturbations in glycerophospholipid and fatty acid metabolism pathways than that with polymyxin B alone. This highlights the unique antimicrobial mode of action of ivacaftor. Pathway analysis revealed that in combination treatment, polymyxin B mediated killing is elevated by ivacaftor, largely due to the inhibition of cell envelope biogenesis via suppression of key membrane lipid metabolites (e.g., sn-glycerol 3-phosphate and sn-glycero-3-phosphoethanolamine) as well as perturbations in peptidoglycan and lipopolysaccharide biosynthesis. Furthermore, significant perturbations in the levels of amino sugars and nucleotide sugars, glycolysis, the tricarboxylic acid cycle, and pyrimidine ribonucleotide biogenesis were observed with the combination treatment. These findings provide novel mechanistic information on the synergistic antibacterial activity of polymyxin–ivacaftor combination.